The terms traditional “populations” and “communities” and the appropriation of the concepts in the Amazon reality - Roberta Rowsy Amorim de Castro; Myriam Cyntia Cesar de Oliveira (Mundo Amazonico, 2016)
This paper aims to review the use of the terminology traditional “populations” and “communities”, highlighting the ambiguities of their uses and appropriation of both concepts in the Amazon reality. The work is the result of a literature search, where surveys have been conducted on the subject. In literature the use of the terms traditional “population” and “communities” it seems to be more of a semantic preference than epistemological and conceptual distances, since the authors use both terms, usually with the same connotation, although there are criticisms related the use of terminology. In Brazilian legislative and legal proceedings there is the use of two terms, as in the case of the National Protected Areas System (Law N° 9.985/2000) and Decree 6040/2007, which prevails in the first the term “populations” and in the second, “peoples and communities”, which does not reflect, however, significant differences in how the definitions of the characteristics of these traditional groups. In the scenario of Amazon biological and cultural diversity, the appropriation of both definitions “population” and “community” contributes to the understanding of social collectivities categories that fight for recognition and to maintain their way of life.